Evaluasi Program Pemberian Tablet Tambah Darah pada Remaja Putri di Jakarta Timur - Mira Krisma Yudina; Adhila Fayasari (Sarana Ilmu Indonesia (salnesia), 2020)
In Indonesia, anemia in adolescents increased from 37.1% in 2013 to 48.9% in 2018, with the proportion of anemia in the age group 15-24 years and 25-34 years. Female adolescents who have anemia will be at risk of anemia during pregnancy, at risk of giving birth to LBW, and stunting. This study was to evaluate an iron tablet supplementation program for female adolescents in Pasar Rebo Health Care. This study was evaluation research that used the qualitative method with purposive sampling in January - February 2020. A qualitative study was conducted by in-depth interviews with nutritionists, health teachers, school administrators, and female adolescents. Data were analyzed by content analysis, included input, process, and output. Quantitative data were also collected which is hemoglobin and iron tablet compliance. At the input stage, there were discrepancies in the facilities and infrastructure. At the process, stage nonconformities occur in distribution, monitoring, recording, and reporting. At the output, stage nonconformities occur in target accuracy, time, and distribution. There were still incompatibilities in its implementation in Pasar Rebo Health Care.